Edwin B. Wilson and the rise of mathematical economics in America, 1920-1940 - Juan Carvajalino (Duke University, Center for the History of Political Economy (CHOPE), 2017)
In the paper, Edwin B. Wilson's influence on the rise of mathematical economics in America between the 1920s and 1940s is explored. The focus is laid on showing how on the grounds of his foundational ideas about science Wilson worked at the organizational and educational fronts to modernize economics, at this at three levels. First, the paper shows the ways in which around 1930 Wilson was key, at the nationwide level, in the constitution of the first organized community of American mathematical economists, which he established within the well-recognized scientific community of the American Association for the Advancement of Science. In the way, the paper traces Wilson's crucial role in the origins of the Econometric Society and bears new lights on the constitution of the econometric movement. Second, the paper reconstructs Wilson's leadership in promoting and establishing the first program in advanced mathematical and statistical economics at the more local level of Cambridge at Harvard. He offered two courses to economists, Mathematical Economics and Mathematical Statistics, in which he respectively taught Gibbs's thermodynamics systems and numerical mathematics and analytical statistics. In his courses, willing to interconnect Viflredo Pareto's and Wesley Mitchell's economics, Wilson emphasized that a sound scientific attitude required connecting economics with data, if only in idealized conditions. Finally, the paper argues that Wilson's lasting influence in economics took shape at a more personal level, through his influence on Paul Samuelson, one of his students at Harvard. Samuelson wrote his thesis (1940) and subsequently Foundations of Economic Analysis (1947) in a Wilsonian style.
Keywords: B10; B20; B23; B31; 330; E. B. Wilson; Samuelson; Gibbs; Mathematics is a Language; AAAS; Econometric Society; Harvard